Zwischen Gentrification und Abwärtsspirale: Sozialräumliche Differenzierung in Wohnquartieren sächsischer Großstadtregionen Ende der 1990er Jahre - Herfert, Günter (Raumforschung und Raumordnung | Spatial Research and Planning, 2003)
Based on a comparative analysis of different types of housing quarters in the large city regions Leipzig, Dresden and Chemnitz in Saxony, the question was considered to what extent the socio-spatial division in the city regions has already taken place at the end of the 1990’s, how high the degree of satisfaction is among the inhabitants of the housing quarters and which development trends could result from the potential intentions to move out. As a result of the great dynamics of selective migrations/moves it became clear that the social segregation of the housing quarters is already far advanced. In addition to the forecast developments in the large housing estates, where a process of decline is partly already reinforcing itself continuously, further problematic developments of housing quarters are emerging in the ordinary areas from the period of industrial expansion and_ — which has been completely ignored in previous considerations so far_ — in some new suburban housing estates.